THE EFFECT OF STORING WHEAT GRAIN IN OPEN WAREHOUSES ON THE "AGING" PROCESS OF BREAD PRODUCTS - Kanoatov, Xayrullo (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article presents an analysis of the influence of wheat grain storage in open warehouses on the aging process of bakery products. The purpose of the studyduring the post-harvest ripening period of wheat grainohBread products stored in waste warehousesThe study consists of a comparative analysis of the effect of the “staleness” process. The AP - 4/1 penetrometer method, which characterizes the most widespread physical and mechanical properties, was used to assess the degree of staleness of bread. Closedgrain stored in warehouseThe volume of bread produced from the flour taken from the sample is 30 - 40 cm3, the relative volume is 0.21 - 0.28 g/cm3, the porosity of the kernel is 2 %, and the organoleptic quality of the bread is 3 - 4 points higher than the others, which indicates that storing wheat grain in closed warehouses during the ripening period after harvest is of great technological importance. It was found that the staleness of bread is related to the technological properties of flour. The interaction of starch and protein, which provide the technological properties of flour, reduces the rate of staleness, but is of less importance than starch retrogradation. The interaction of starch and protein, which provide its technological properties, reduces the rate of staleness, but is less important than starch retrogradation.